Curing reagent and method for chemically fixing pollutants in ardealite
By using solid waste containing ammonium, magnesium-based components and calcium-based components to treat phosphogypsum, the complex treatment process and high drug cost are solved, and the efficient fixation of pollutants and the improvement of mechanical strength is achieved. It is suitable for roadbed materials and other purposes.
Patent Information
- Application Number
- CN202411932735.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the process of phosphogypsum treatment is complicated, the treatment process is prone to secondary pollution and high drug costs.
The curing reagent composed of ammonium-containing solid waste, magnesium-based components and calcium-containing alkaline components are used to process the phosphogypsum through the process of dry/wet material mixing, casting molding and chemical consolidation to achieve efficient fixation of hydrogen protons, phosphate and fluoride ions in the phosphogypsum.
It has achieved efficient fixation of pollutants in phosphogypsum, formed a solid body with high mechanical strength, and is suitable for use in roadbed materials and other purposes. It has low reagent cost and simple process, and has promotion and application value.
Smart Images

Figure CN119707377A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for treating phosphogypsum, in particular to a solidifying agent and method for chemically fixing pollutants such as phosphorus and fluorine in phosphogypsum, and belongs to the technical field of solid waste treatment. Background Art
[0002] In the wet process of phosphoric acid preparation, a large amount of industrial solid byproduct phosphogypsum is produced after the reaction of phosphate ore with sulfuric acid. The chemical composition of phosphogypsum mainly includes CaO, sulfuric acid, SiO2, Al2O3, Fe2O3, P2O5 and F. Since phosphogypsum contains a large amount of impurities, it affects the performance of gypsum products, restricts the reuse of phosphogypsum, and causes the continuous storage of phosphogypsum, which not only occupies a large amount of land, but also has serious harm to the surrounding ecological environment.
[0003] The main pollutants in phosphogypsum include: pH, phosphorus and fluorine. The pH of phosphogypsum produced under different process conditions is different, with the lowest being 1.9. This is because the phosphorus in phosphogypsum will acidify the environment and affect the activity of microorganisms in the soil and the soil structure, which is not only not conducive to plant growth, but also affects the soil ecosystem and agricultural production. The phosphorus in phosphogypsum mainly exists in the form of soluble phosphorus, sparingly soluble phosphorus and eutectic phosphorus. Soluble phosphorus will react with calcium ions to form sparingly soluble calcium salts, which will hinder the hydrolysis and further hydration of dihydrate gypsum, reduce the strength of building materials and cement, and cause powdering and frosting on the surface of the products, affecting the performance of phosphogypsum as a building material. In addition, after the soluble fluorine in phosphogypsum flows into water bodies and soil, excessive intake of human body through food and drinking water will seriously affect health and even cause fluorosis. Fluorine exists in phosphogypsum mainly in two forms: soluble fluorine and insoluble fluorine. Soluble fluorine will weaken the interaction between phosphogypsum molecules. When the content reaches a certain level, it will reduce the compressive and flexural strength of phosphogypsum, thereby affecting its performance as a building material.
[0004] At present, the harmless treatment methods for phosphogypsum include: water washing method (publication number: CN118180122A), heat treatment method (publication number: CN118856874A), consolidation method (publication number: CN111138099A), etc. However, these methods still have the following problems: 1) Water washing method, dihydrate gypsum with stable performance and impurity content that meets relevant standards must be obtained after water washing, which requires higher process requirements. At the same time, the secondary pollution problem caused by the water washing process must be treated for the generated water washing wastewater, which also increases the cost of phosphogypsum recycling. 2) Heat treatment method, by high-temperature treatment of phosphogypsum, eutectic phosphorus can be converted into pyrophosphate, and organic matter is volatilized at high temperature, thereby improving the purity and performance of phosphogypsum. However, the heat treatment method has high energy consumption, high cost, and high equipment requirements, which limits its wide application. Although the flash method (publication number: CN205348215U) is a new heat treatment method with the characteristics of fast heating speed, uniform heating, and rapid reaction, it needs to reach high temperature in a short time and accurately control temperature and atmosphere conditions. Therefore, it has extremely high requirements on the performance and precision of the equipment, and requires precise control of process parameters such as temperature, atmosphere, and material residence time, otherwise it will easily lead to poor treatment effects. There is also a risk of producing polluting gases such as sulfur dioxide and hydrogen fluoride. 3) Consolidation method. The existing chemical consolidation method requires the use of a large amount of chemical agents, such as some high-priced metal salts of calcium chloride used to consolidate phosphorus and fluorine. The procurement cost of these agents is relatively high. For large-scale phosphogypsum treatment, the overall cost of phosphogypsum treatment is increased. It is difficult to completely remove or fix pollutants, and some chemical consolidation needs to be carried out under specific temperature and pressure conditions, which increases the energy consumption compared to other methods.
[0005] Therefore, seeking a method for stabilizing phosphogypsum pollutants with easily available raw materials, simple production process and low manufacturing cost has important application value for the reuse of phosphogypsum. Summary of the invention
[0006] In view of the problems in the prior art of treating phosphogypsum, such as complex process, easy generation of secondary pollution in the treatment process and high cost of reagents, the first object of the present invention is to provide a solidifying agent for chemically fixing pollutants in phosphogypsum, which can simultaneously realize the efficient fixation of pollutants such as hydrogen protons, phosphate groups and fluoride ions in phosphogypsum, and can solidify with phosphogypsum to form a solidified body with high mechanical strength, which is beneficial for subsequent use as roadbed material, etc. In particular, the raw materials used in the solidifying agent are mainly solid waste, so as to achieve the purpose of waste treatment and coordinated disposal of multiple solid wastes, thereby avoiding environmental problems caused by solid waste storage.
[0007] The second object of the present invention is to provide a method for chemically fixing pollutants in phosphogypsum, which uses a special curing agent and combines the process of dry / wet material mixing + casting molding + chemical consolidation to treat the phosphogypsum, which can increase the pH of the phosphogypsum system and utilize the Ca in the curing agent to fix the pollutants in the phosphogypsum. 2+ NH 4+ Mg 2+ The free phosphate and fluoride ions in phosphogypsum are chemically fixed to form stable minerals, and a consolidated body with high mechanical strength is obtained to meet the purpose of roadbed materials. The efficient fixation of pollutants in phosphogypsum is truly realized, and the reagent cost is low and the solidification process is simple, which is conducive to promotion and application.
[0008] In order to achieve the above technical objectives, the present invention provides a solidification agent for chemically fixing pollutants in phosphogypsum, which includes ammonium-containing solid waste, magnesium-based components and calcium-containing alkaline components.
[0009] In view of the fact that phosphogypsum is acidic and contains soluble phosphates and soluble fluorides, the present invention uses a solidifying agent composed of calcium-containing alkaline components, ammonium-containing solid waste and magnesium-based components as main raw materials, which can not only increase the pH of phosphogypsum, but also chemically fix free phosphate and fluoride ions to achieve stabilization of phosphogypsum, and at the same time form a solid body with phosphogypsum that meets the mechanical strength requirements of roadbed materials. The calcium-containing alkaline components in the solidifying agent mainly provide alkaline components such as active calcium oxide to adjust the pH of the system, which can not only neutralize the acid components in phosphogypsum, but also provide a favorable pH environment for the solidification of phosphate and fluoride ions. The ammonium-containing solid waste and magnesium-based components mainly provide ammonium ions and magnesium ions to react with free phosphates to produce stable ammonium magnesium phosphate (the main reaction formula is as follows: PO4 3- +NH4 + +Mg 2+ +6H2O=MgNH4PO4·6H2O), and at the same time, the calcium ions in the calcium-containing alkaline solid waste and the free fluoride ions in the phosphogypsum are converted into stable calcium fluoride (the main reaction formula is as follows: Ca 2+ +2F - =CaF2), thereby realizing the transformation of soluble phosphorus and fluorine in phosphogypsum into stable phosphorus and fluorine, while adjusting the pH of the system to alkaline, so that the heavy metal ions in various solid wastes can be stabilized.
[0010] As a preferred solution, the ammonium-containing solid waste includes electrolytic manganese slag. Electrolytic manganese slag contains free ammonium ions, which easily release ammonia gas, and is therefore one of the important pollutants of electrolytic manganese slag. The present invention can use it as an ammonium source, which is also an effective means to achieve the fixation of ammonium ions in electrolytic manganese slag. At the same time, electrolytic manganese slag also contains active calcium oxide and metal oxides such as manganese and iron. The Mn element can promote the formation of porous structure through chemical reactions such as oxidation-reduction, and has more adsorption active sites. In addition, the binary metal oxide or hydroxide of Fe-Mn can also increase the adsorption of phosphate, which is beneficial to promote the phosphate solidification effect.
[0011] As a preferred solution, the magnesium series component includes serpentine and / or magnesium sulfate. The magnesium series component mainly provides magnesium ions, preferably natural serpentine minerals, which are derived from ore dressing tailings.
[0012] As a preferred solution, the calcium-containing alkaline component includes at least one of red mud, fly ash, carbide slag, and soft soil curing agent; the soft soil curing agent includes cement, lime and fly ash. The preferred calcium-containing alkaline component includes carbide slag or soft soil curing agent. The specific composition ratio of the soft soil curing agent is: 8-12% cement clinker, 5-15% steel slag, 30-35% fly ash, 40-45% mineral powder, and 2-4% filling masterbatch, measured with the total mass as 100%. For example: 9.71% cement clinker, 10.68% steel slag, 33.98% fly ash, 42.72% mineral powder, and 2.91% filling masterbatch. Among them, the main component of the filling masterbatch is light calcium carbonate, which can fill the gaps between soft soil particles, increase the density of the soil, and improve the strength of the solidified soil. The preferred soft soil solidifying agent is a composite alkaline solidifying agent, which can provide ion exchange, cementation, pH control and other functions during the consolidation process, thereby improving the solidification effect of harmful components in phosphogypsum.
[0013] As a preferred solution, the ammonium-containing solid waste and the magnesium-based component are measured according to a molar ratio of ammonium ions to magnesium ions of (1-3): (0.8-2.5). Ammonium ions and magnesium ions can form stable magnesium ammonium phosphate (struvite) with phosphate, so controlling the ratio of ammonium-containing solid waste and magnesium-based components to adjust the ratio of ammonium ions to magnesium ions within an appropriate range is conducive to the formation of magnesium ammonium phosphate.
[0014] As a preferred solution, the amount of the alkaline component is measured to adjust the pH of the phosphogypsum system to 8-13. If the amount of the calcium-containing alkaline component is too high, the alkalinity of the system is too high, and the Mg content in the composite material is too high. 2+The form of Mg(OH)2 is present, which reduces the amount of stable phosphorus, resulting in phosphorus being mainly in an unstable form, and at the same time causing its surface to become brittle and peel off due to alkalinity. If the amount of calcium-containing alkaline components is too low, it is not only not conducive to the fixation of free fluoride ions in the phosphogypsum system, but also difficult to adjust the pH value to the alkaline environment that is most conducive to the formation of struvite. The amount of the alkaline component is measured to adjust the pH of the phosphogypsum system to 9-10.5.
[0015] The present invention also provides a method for chemically fixing pollutants in phosphogypsum, which comprises fully mixing the phosphogypsum with the reagent to obtain a dry material; adding water to the dry material and stirring it to obtain a wet material; and sequentially casting, curing and drying the wet material.
[0016] As a preferred solution, the ratio of the curing agent to the phosphogypsum is controlled to be (1-3): (0.8-2.5): 1, and the curing agent contains calcium alkaline components to adjust the pH of the phosphogypsum system to 8-13. The amount of curing agent added affects the compressive strength of the phosphogypsum solid body. Therefore, in order to achieve effective fixation of harmful components in the phosphogypsum and obtain a solid body with high consolidation strength, it is necessary to control the ratio of the reagents within a suitable range. In a further preferred solution, the ratio of the curing agent to the phosphogypsum is controlled to be (1.1-2.0): (1.1-2.0): 1. It is further preferred that the curing agent contains calcium alkaline components to adjust the pH of the phosphogypsum system to 9-10.5. The phosphogypsum system refers to a mixed system of a curing agent and phosphogypsum.
[0017] As a preferred solution, the liquid-solid ratio of the wet material is 3-8 mL / 10 g. The leaching rate of phosphorus and fluorine in the phosphogypsum solid body decreases with the increase of the water-cement ratio, but a too high water-cement ratio will reduce the strength of the composite material, and a too low water-cement ratio will affect the hydration reaction process, which is not conducive to the reuse of phosphogypsum stabilized materials. By properly selecting the system water-cement ratio, the hydration reaction can be promoted and the system stability can be improved.
[0018] The leaching concentrations of phosphorus and fluorine in the phosphogypsum of the present invention are 100-800.00 mg / L and 100-600.00 mg / L respectively.
[0019] The ammonia nitrogen leaching concentration in the electrolytic manganese slag of the present invention is 200-1000 mg / L.
[0020] Compared with the prior art, the present invention has the following beneficial technical effects: The solidifying agent provided by the present invention is used for solidifying phosphogypsum, and can realize the efficient fixation of pollutants such as hydrogen protons, phosphate radicals and fluoride ions in phosphogypsum. At the same time, it can be solidified with phosphogypsum to form a solidified body with high mechanical strength, which is beneficial for subsequent use as roadbed material and the like. Moreover, the raw materials used in the solidifying agent are mainly existing solid wastes, so as to achieve the purpose of waste treatment with waste and coordinated disposal of multiple solid wastes, thereby avoiding environmental problems caused by solid waste storage.
[0021] The method for chemically fixing pollutants in phosphogypsum provided by the present invention uses a special reagent and combines the process flow of dry / wet material mixing + casting molding + chemical consolidation to treat the phosphogypsum, which can increase the pH of the phosphogypsum system and utilize the Ca in the reagent to 2+ 、N 4+ Mg 2+ The free phosphate and fluoride ions in phosphogypsum are chemically fixed to form stable minerals, and a consolidated body with high mechanical strength is obtained to meet the purpose of roadbed materials. The efficient fixation of pollutants in phosphogypsum is truly realized, and the reagent cost is low and the solidification process is simple, which is conducive to promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the XRD characterization analysis diagram of the chemical consolidation body of phosphogypsum-electrolytic manganese slag-serpentine cured for 14 days in Example 1.
[0023] Figure 2 This is the XRD characterization analysis diagram of the chemical consolidation body of phosphogypsum-electrolytic manganese slag-carbide slag-magnesium salt cured for 14 days in Example 2. DETAILED DESCRIPTION
[0024] The following specific examples are intended to further illustrate the present invention, but the following examples do not limit the scope of the claims of the present invention.
[0025] The phosphogypsum used in the following specific examples comes from a phosphoric acid plant in Yichang, Hubei Province. It is screened using a sieve with a particle size of 80-200 mesh, and the composition of the phosphogypsum is determined using XRF. Tables 1-4 show the main components of the experimental raw materials.
[0026]
[0027]
[0028]
[0029] The cement clinker involved in the following embodiments is the common model P.O42.5 in the market. The detection methods involved refer to the "Solid Waste Leaching Toxicity Leaching Method Horizontal Oscillation Method" (HJ 557-2010), "Water Quality Total Phosphorus Determination Ammonium Molybdate Spectrophotometric Method" (GB 11893-89), "Soil Water-soluble Fluoride and Total Fluoride Determination Ion Selective Electrode Method" (HJ 873-2017).
[0030] The soft soil solidifying agent involved in the following embodiments is a commercial product, and its specific composition is: 9.71% cement clinker, 10.68% steel slag, 33.98% fly ash, 42.72% mineral powder, and 2.91% light calcium carbonate.
[0031] The leaching concentrations of phosphorus and fluorine in the phosphogypsum of the present invention are 154 mg / L and 201 mg / L respectively.
[0032] The ammonia nitrogen leaching concentration in the electrolytic manganese slag of the present invention is 301 mg / L.
[0033] Example 1 The curing agent consists of electrolytic manganese slag, serpentine and soft soil curing agent.
[0034] During the phosphogypsum process, the N (ammonium ion) / P (phosphate) ratio was controlled to be 3:1, 2.5:1, 2:1, 1.5:1, and 1.0:1, the Mg (magnesium ion) / P (phosphate) ratio was 1:1, the water-cement ratio was 0.42, the soft soil curing agent dosage (relative to the total dry material dosage) was 10% (the pH of the adjustment system was adjusted to 8-9), the dry mixing time was 5 min, the wet mixing time was 10 min, and casting was used. The phosphorus leaching concentration of each consolidation body was tested after curing for the corresponding number of days. The effect of different N / P on the phosphorus curing rate of the composite material is shown in Table 5.
[0035]
[0036] It can be seen from Table 4 that with the increase of N / P ratio, the phosphorus curing rate increases significantly. When N / P reaches 2.5, the phosphorus curing rate of the composite material is 99.12% after 14 days.
[0037] After 3 days of curing, the unconfined compressive strength of the consolidation bodies formed by different N / P ratios were 9.10MPa, 8.75MPa, 8.45MPa, 8.35MPa, and 7.75MPa, respectively. With the increase of electrolytic manganese slag content, the phosphorus solidification effect in phosphogypsum was slightly improved. The formed consolidation body can be used as a mine filling material, and its strength after solidification can be used to support the rock mass around the mine. At the same time, the solidification effect on phosphorus can prevent the phosphorus element from seeping out in the mine environment and reduce the pollution of groundwater.
[0038] Compared with Examples 2 to 10, Example 1 can accelerate the hydration reaction process and improve the degree of hydration reaction by adding a soft soil curing agent, so the compressive strength is higher and the application range is wider.
[0039] Example 2 The curing agent consists of electrolytic manganese slag, carbide slag and magnesium sulfate.
[0040] During the phosphogypsum treatment process, the N (ammonium ion) / P (phosphate) ratio was controlled to be 1.23, the Mg (magnesium ion) / P (phosphate) ratio was controlled to be 1.18, the water-cement ratio was 0.5, the carbide slag content (relative to the total dry material content) was 2% (the system pH reached 8.29~8.69), the dry mixing time was 5 min, and the wet mixing time was 10 min. Casting was used for both, and the phosphorus and fluorine leaching concentrations of each consolidation body were tested after curing for the corresponding number of days. After 3 days of curing at room temperature, the phosphorus and fluorine curing rates of the consolidation body can reach 95.48% and 95.27% respectively. After 14 days of curing at room temperature, the unconfined compressive strength of the consolidation body is 1.01MPa.
[0041] Example 3 The curing agent consists of electrolytic manganese slag, carbide slag and magnesium sulfate.
[0042] During the phosphogypsum treatment process, the N (ammonium ion) / P (phosphate) was controlled to be 1.23, the Mg (magnesium ion) / P (phosphate) was controlled to be 1.18, the water-cement ratio was 0.5, the amount of calcium carbide slag (relative to the total dry material amount) was 3% (the system pH reached 9.19~9.87), the dry mixing time was 5 min, and the wet mixing time was 10 min. Casting was used for both, and the phosphorus and fluorine leaching concentrations of each consolidation body were tested after curing for the corresponding number of days. After 3 days of curing at room temperature, the phosphorus and fluorine curing rates of the consolidation body can reach 99.98% and 98.89% respectively. After 14 days of curing at room temperature, the unconfined compressive strength of the consolidation body is 1.18MPa.
[0043] Example 4 The curing agent consists of electrolytic manganese slag, carbide slag and magnesium sulfate.
[0044] During the phosphogypsum treatment process, the N (ammonium ion) / P (phosphate) ratio was controlled to be 1.23, the Mg (magnesium ion) / P (phosphate) ratio was 1.18, the water-cement ratio was 0.5, the carbide slag content (relative to the total dry material content) was 4% (the system pH reached 11.40~11.89), the dry mixing time was 5 min, and the wet mixing time was 10 min. Casting was used for both, and the phosphorus and fluorine leaching concentrations of each consolidation body were tested after curing for the corresponding number of days. After 3 days of curing at room temperature, the phosphorus and fluorine curing rates of the consolidation body can reach 99.58% and 97.83% respectively. After 14 days of curing at room temperature, the unconfined compressive strength of the consolidation body is 1.20MPa.
[0045] Example 5 The curing agent consists of electrolytic manganese slag, carbide slag and magnesium sulfate.
[0046] During the phosphogypsum treatment process, the N (ammonium ion) / P (phosphate) ratio was controlled to be 1.23, the Mg (magnesium ion) / P (phosphate) ratio was controlled to be 1.18, the water-cement ratio was 0.5, the carbide slag content (relative to the total dry material content) was 5% (the system pH reached 12.27~12.38), the dry mixing time was 5 min, and the wet mixing time was 10 min. Casting was used for both, and the phosphorus and fluorine leaching concentrations of each consolidation body were tested after curing for the corresponding number of days. After 3 days of curing at room temperature, the phosphorus and fluorine curing rates of the consolidation body can reach 99.28% and 98.13%, respectively. After 14 days of curing at room temperature, due to the excessive amount of carbide slag and the strong alkalinity of the system, the surface of the consolidation body was brittle and alkali-eluting, and the unconfined compressive strength of the consolidation body was 1.02MPa.
[0047] Example 6 The curing agent consists of electrolytic manganese slag, carbide slag and magnesium sulfate.
[0048] During the phosphogypsum treatment process, the N (ammonium ion) / P (phosphate) ratio was controlled to be 1.23, the Mg (magnesium ion) / P (phosphate) ratio was controlled to be 1.18, the water-cement ratio was 0.5, the carbide slag content (relative to the total dry material content) was 6% (the system pH reached 12.31~12.56), the dry mixing time was 5 min, and the wet mixing time was 10 min. Casting was used for both, and the phosphorus and fluorine leaching concentrations of each consolidation body were tested after curing for the corresponding number of days. After 3 days of curing at room temperature, the phosphorus and fluorine curing rates of the consolidation body can reach 97.23% and 98.06%, respectively. After 14 days of curing at room temperature, due to the excessive amount of carbide slag and the strong alkalinity of the system, the surface of the consolidation body was embrittled and alkali-eluted, and the unconfined compressive strength of the consolidation body was 0.86MPa.
[0049] Example 7 The curing agent consists of electrolytic manganese slag, carbide slag and magnesium sulfate.
[0050] During the phosphogypsum treatment process, the N (ammonium ion) / P (phosphate) ratio was controlled to be 1.23, the Mg (magnesium ion) / P (phosphate) ratio was controlled to be 0.8, the water-cement ratio was controlled to be 0.5, the amount of carbide slag (relative to the total dry material amount) was controlled to be 3% (the system pH reached 9.19~9.87), the dry mixing time was 5 min, and the wet mixing time was 10 min. Casting was used for both, and the phosphorus and fluorine leaching concentrations of each consolidation body were tested after curing for the corresponding number of days. After 3 days of curing at room temperature, the phosphorus and fluorine curing rates of the consolidation body can reach 99.33% and 98.82% respectively. After 14 days of curing at room temperature, the unconfined compressive strength of the consolidation body is 1.03MPa.
[0051] Example 8 The curing agent consists of electrolytic manganese slag, carbide slag and magnesium sulfate.
[0052] During the phosphogypsum treatment process, the N (ammonium ion) / P (phosphate) ratio was controlled to be 1.23, the Mg (magnesium ion) / P (phosphate) ratio was 1.0, the water-cement ratio was 0.5, the carbide slag content (relative to the total dry material content) was 3% (the system pH reached 9.19~9.87), the dry mixing time was 5 min, and the wet mixing time was 10 min. Casting was used for both, and the phosphorus and fluorine leaching concentrations of each consolidation body were tested after curing for the corresponding number of days. After 3 days of curing at room temperature, the phosphorus and fluorine curing rates of the consolidation body can reach 99.68% and 98.81% respectively. After 14 days of curing at room temperature, the unconfined compressive strength of the consolidation body is 1.22MPa.
[0053] Example 9 The curing agent consists of electrolytic manganese slag, carbide slag and magnesium sulfate.
[0054] During the phosphogypsum treatment process, the N (ammonium ion) / P (phosphate) ratio was controlled to be 1.23, the Mg (magnesium ion) / P (phosphate) ratio was 1.3, the water-cement ratio was 0.5, the amount of carbide slag (relative to the total dry material content) was 3% (the system pH reached 9.19~9.87), the dry mixing time was 5 min, and the wet mixing time was 10 min. Casting was used for both, and the phosphorus and fluorine leaching concentrations of each consolidation body were tested after curing for the corresponding number of days. After 3 days of curing at room temperature, the phosphorus and fluorine curing rates of the consolidation body can reach 99.88% and 98.91% respectively. After 14 days of curing at room temperature, the unconfined compressive strength of the consolidation body is 1.26MPa.
[0055] Example 10 The curing agent consists of electrolytic manganese slag, carbide slag and magnesium sulfate.
[0056] During the phosphogypsum treatment process, the N (ammonium ion) / P (phosphate) was controlled to be 1.23, the Mg (magnesium ion) / P (phosphate) was controlled to be 1.18, the water-cement ratio was 0.5, the carbide slag content (relative to the total dry material content) was 4% (the system pH reached 9.19~9.87), the dry mixing time was 5 min, and the wet mixing time was 10 min. Casting was used for both, and the phosphorus and fluorine leaching concentrations of each consolidation body were tested after curing for the corresponding number of days. After 3 days of curing at room temperature, the phosphorus and fluorine curing rates of the consolidation body can reach 99.95% and 98.43% respectively. After 14 days of curing at room temperature, the unconfined compressive strength of the consolidation body is 1.19MPa.
Claims
1. A solidifying agent for chemically fixing pollutants in phosphogypsum, characterized in that: Including ammonium-containing solid waste, magnesium-containing components and calcium-containing alkaline components.
2. The solidifying agent for chemically fixing phosphorus and fluorine in phosphogypsum according to claim 1, characterized in that: The ammonium-containing solid waste includes electrolytic manganese slag.
3. The solidifying agent for chemically fixing pollutants in phosphogypsum according to claim 1, characterized in that: The magnesium series components include serpentine and / or magnesium sulfate.
4. The solidifying agent for chemically fixing pollutants in phosphogypsum according to claim 1, characterized in that: The calcium-containing alkaline component includes at least one of red mud, fly ash, carbide slag and soft soil solidifying agent; the soft soil solidifying agent includes cement, lime and fly ash.
5. A solidifying agent for chemically fixing pollutants in phosphogypsum according to claim 1, 2 or 3, characterized in that: The ammonium-containing solid waste and the magnesium-based components are measured according to a molar ratio of ammonium ions to magnesium ions of (1-3): (0.8-2.5).
6. A solidifying agent for chemically fixing pollutants in phosphogypsum according to claim 1 or 4, characterized in that: The amount of the alkaline component is measured to adjust the pH of the phosphogypsum system to 8-13.
7. A method for chemically fixing pollutants in phosphogypsum, characterized in that: The phosphogypsum is fully mixed with the curing agent according to any one of claims 1 to 6 to obtain a dry material; the dry material is added with water and stirred to obtain a wet material; the wet material is cast, cured and dried in sequence.
8. The method for chemically fixing pollutants in phosphogypsum according to claim 7, characterized in that: The ratio of the curing agent to the phosphogypsum is controlled to have a molar ratio of ammonium ions and magnesium ions in the curing agent to phosphate in the phosphogypsum of (1-3):(0.8-2.5):1, and the curing agent contains a calcium alkaline component to adjust the pH of the phosphogypsum system to 8-13.
9. The method for chemically fixing pollutants in phosphogypsum according to claim 7, characterized in that: The liquid-to-solid ratio of the wet material is 3-8 mL / 10 g.
Citation Information
Patent Citations
Curing agent and curing method for phosphogypsum waste residues
CN111138099A
Method for washing and purifying phosphogypsum
CN118180122A
Intelligent cooling device of calcining furnace for phosphogypsum calcination
CN118856874A
Sulphur, ardealite dodge and burn kiln basis
CN205348215U